2018
DOI: 10.1111/bph.14548
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of kinetics of human cytochrome P450s involved in bioactivation of flucloxacillin: inhibition of CYP3A‐catalysed hydroxylation by sulfaphenazole

Abstract: Background and PurposeThe aim of this study was to characterize the human cytochrome P450s (CYPs) involved in oxidative bioactivation of flucloxacillin to 5‐hydroxymethyl flucloxacillin, a metabolite with high cytotoxicity towards biliary epithelial cells.Experimental ApproachThe CYPs involved in hydroxylation of flucloxacillin were characterized using recombinant human CYPs, pooled liver microsomes in the presence of CYP‐specific inhibitors and by correlation analysis using a panel of liver microsomes from 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 49 publications
(77 reference statements)
0
8
0
Order By: Relevance
“…To quantify the contribution of the different CYP enzymes in VRC N -oxidation, two different experimental approaches were applied. In the first approach, the specific CYP inhibitors, loratadine (10 µM, CYP2C19), sulfaphenazole (10 µM, CYP2C9) and ketoconazole (0.1 µM, CYP3A4), as well as a mixture of the three, were added to VRC (0.5, 1, 2, 3 µM) incubations in HLM ( n = 3, t reac .= 15 and 25 min) [ 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. The reaction velocities at the respective substrate concentrations in the presence and absence of the inhibitor were used to assess the contribution to NO formation.…”
Section: Methodsmentioning
confidence: 99%
“…To quantify the contribution of the different CYP enzymes in VRC N -oxidation, two different experimental approaches were applied. In the first approach, the specific CYP inhibitors, loratadine (10 µM, CYP2C19), sulfaphenazole (10 µM, CYP2C9) and ketoconazole (0.1 µM, CYP3A4), as well as a mixture of the three, were added to VRC (0.5, 1, 2, 3 µM) incubations in HLM ( n = 3, t reac .= 15 and 25 min) [ 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. The reaction velocities at the respective substrate concentrations in the presence and absence of the inhibitor were used to assess the contribution to NO formation.…”
Section: Methodsmentioning
confidence: 99%
“…of the isoxazolyl-penicillin type is used to treat Gram-positive bacterial infections. Although CYP3A4 is involved in the metabolism of flucloxacillin, the drug itself does not show inhibition of CYP P450 isoenzymes, as shown by in vitro assays [6][7][8]. However, several cases have been reported in which flucloxacillin appeared to decrease levels of drugs metabolized by CYP3A4, such as voriconazole, cyclosporin A, and quinidine [8][9][10][11].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…The pathogenesis of idiosyncratic DILI has often been related to CYP dependent drug metabolism, although the respective DILI was not assessed regarding causality for the drug under consideration study, nor was there any verification that the drug was really metabolized by CYP, and the CYP isoform involved in the metabolism of the drug commonly remained unconsidered. Based on published data [ 64 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 ], a recent analysis on drugs most implicated in idiosyncratic DILI assessed by RUCAM showed that only a portion of the drugs were substrates of hepatic microsomal CYP ( Table 3 ) [ 54 ].…”
Section: Overview On Molecular Toxicology In Human Idiosyncratic Dilimentioning
confidence: 99%
“…An assumed HLA association of liver injury by Amoxicillin-clavulanate has been proposed already in 1999, but results remained vague because cases were not assessed using RUCAM. Of clinical significance, Amoxicillin clavulanate was at rank #1 and Flucloxacillin at rank #2 among the drugs most implicated in RUCAM based DILI worldwide ( Table 3 ), and regarding mechanistic steps, drug metabolism via CYP is not essential for HLA mediated DILI because Amoxicillin clavulanate is not metabolized by CYP ( Table 3 ) [ 72 ] as opposed to Flucloxacillin that is metabolized ( Table 3 ) [ 73 ].…”
Section: Hepatic Immune Systemmentioning
confidence: 99%